Auditory training app validation. (24th June 2020) - Maia, F; Jesus, V; Mateus, C; Paulo, S; Marcelino, L; Serrano, M
Abstract: Introduction One of the main hearing complaints is the difficulty to perceive speech in noisy environments. This complaint gets worse with ageing at which cognitive processing speed slows and/or when hearing loss is present. An auditory training can improve speech perception in adverse environments. The use of auditory training software on various digital platforms is becoming a reality. Objectives To validate the auditory training app in European Portuguese with individuals aged between 55 and 64 years old with an approximate average of 20dB of hearing thresholds. Methodology The sample consists in two groups of seven individuals without cognitive problems. One of the groups performed eight auditory training sessions with the application for a period of four weeks and the other group (the control group) did not perform any auditory training session. The evaluation was made in all the individuals with the filtered speech test. The training group was evaluated before, immediately after and after four weeks of the auditory training sessions and the control group was evaluated after four weeks. Results Statistically there is a significant difference between before and immediately after the auditory training in the filtered speech test (p = 0.018). Four weeks after the end of the training the performance of each individual was the same. In the control group there were no significant differences between the two evaluation moments. Conclusion The EVOLLU auditory training app promotes an improvement in the perception of the word in adverse environments that continues even after some time. This is a sign that individuals are applying that learning into their day to day living. The Evollu application can and should be used in the auditory training of individuals aged between 55 to 64 years old.